Reservoir Computing for Healthcare Analytics - S Pathak, Shantanu; Rajeswara Rao, D (International Journal of Engineering and Technology, 2018)
In this data age tools for sophisticated generation and handling of data are at epitome of usage. Data varying in both space and time poses a breed of challenges. Challenges they possess for forecasting can be well handled by Reservoir computing based neural networks. Challenges like class imbalance, missing values, locality effect are discussed here. Additionally, popular statistical techniques for forecasting such data are discussed. Results show how Reservoir Computing based technique outper-forms traditional neural networks.Â Â Â